PENGARUH PUPUK KASCING TERHADAP PERTUMBUHAN DAN HASIL MENTIMUN BABY PADA TANAH ALUVIAL - Muslimin, Uray; Zulfita, Dwi; Santoso, Eddy (Jurnal Sains Pertanian Equator, 2015)
ABSTRACT This research aims to observe the influences of vermicompost fertilizer on baby cucumber growth and yield in aluvial soils. The research project was held in Parit Haji Muksin 2, Sungai raya dalam Subdistrict, Kubu Raya Regency. This research took place from July 1th to August 15th 2014, using Randomized Block Design with a single-factor that includes 6 treatment levels. These treatment levels are: 12g/plant, 27g/plant 42 g/plant 57 g/plant 72 g/plant, and 87g/plant. Each treatment was repeated 4 times. This result showed that vermicompost fertilizer significant effect on root volume (cm3), dry plant weight (g) and time of flowering but not significant effevt on leaf area (cm2), number of fruits (fruit) and fruit weight (g). Key words: aluvial, vermicompost, baby cucumber